2021
DOI: 10.1007/s00068-020-01593-w
|View full text |Cite
|
Sign up to set email alerts
|

The ICON Trauma Study: the impact of the COVID-19 lockdown on major trauma workload in the UK

Abstract: Background The global pandemic caused by SARS-CoV-2 has impacted population health and care delivery worldwide. As information emerges regarding the impact of “lockdown measures” and changes to clinical practice worldwide; there is no comparative information emerging from the United Kingdom with regard to major trauma. Methods This observational study from a UK Major Trauma Centre matched a cohort of patients admitted during a 10-week period of the SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 22 publications
5
22
1
2
Order By: Relevance
“…Despite the limitations of our study, our work demonstrates the need for fast-track emergency surgical services during the pandemic to decrease time to operation and reduce post-operative complication severity. This has been described by other orthopaedic departments globally [25,26].…”
Section: Discussionsupporting
confidence: 57%
“…Despite the limitations of our study, our work demonstrates the need for fast-track emergency surgical services during the pandemic to decrease time to operation and reduce post-operative complication severity. This has been described by other orthopaedic departments globally [25,26].…”
Section: Discussionsupporting
confidence: 57%
“…Although falls are common among older adults, the population most impacted by COVID-19, very few current publications address this topic specifically, especially from an anxiety perspective. However, even though Williams et al [27] noted no significant association between anxiety disorders and falls among prior fallers who were depressed in their study, as observed in a systematic review by Payette et al [28] and Almeida et al [18] who studied 41,098 community dwelling men and women, mean ages 70.0 ± 8.9 years, a falls prevalence of 8.2% that was noted was higher among those who were older, female, and frail. As well, those exhibiting evidence of multiple medication usage and/or fear of falling, plus those with falls related psychological concerns were more likely to fall than those who did not take multiple medications or have any falls associated fears.…”
Section: Resultsmentioning
confidence: 73%
“…Although not explicitly related to anxiety, it has also been shown in an observational study originating from a major United Kingdom trauma centre of patients admitted during a 10-week period starting in March 2020 who were compared to a historical cohort of patients admitted during a similar time period in 2019 that this current cohort was older and more frail with more comorbidities and an increased falls rate. There was also a twofold increase in the risk of mortality in the 2020 cohort, which was explained by injury severity and frailty, when all other variables were controlled [18].…”
Section: Introductionmentioning
confidence: 93%
“…In one report from UK the trauma system itself had been even more overwhelmed by the fact that patients admitted during the COVID-19 pandemic were older, frailer and with higher co-morbidity with associated increased risk of mortality [ 6 ]; while due to reallocation of surgeons in other areas, in order of obligations to take different in-hospital tasks, and due to progressive transmission of the in novel coronavirus (2019-nCoV) among care providers, some surgeons had to take significantly more calls [ 14 ] struggling with burn-out.…”
mentioning
confidence: 99%
“…Although the overall volume of injuries and cases with acute abdominal conditions admitted to the emergency department decreased due to lockdown and containment strategy, new challenges had to be managed [5][6][7][8]; skeletal trauma surgeons reported higher mortality rates in COVID-19 positive patients with hip fractures [9] and an increasing incidence proportion of emergency operations and severe open fractures [10], while emergency general surgeons, to spare resources and protect the population, had to modify their decision making process shifting towards a tailored conservative approach and struggled with more severe cases due to late presentation of patients with acute abdominal conditions [11][12][13].…”
mentioning
confidence: 99%